From disavowal to dialogue: forging collaborative ethical, clinical, and medical approaches to severe and enduring anorexia nervosa - Maryrose Bauschka; Anne Marie O’Melia (Journal of Eating Disorders)
Abstract Anorexia nervosa carries one of the highest mortality rates among psychiatric disorders, yet care pathways for individuals with longstanding, treatment-resistant illness continue to pose significant challenges. Drawing on scholarly critique, lived-experience perspectives, and recent shifts in clinical stance, most notably Dr. Jennifer Gaudiani’s formal published disavowal of the term “terminal anorexia nervosa”, this commentary proposes forward-looking strategies across four domains: terminology, capacity assessment, systemic supports, and integrated care frameworks. We advocate replacing deterministic labels with descriptive terms that honor recovery potential and the full spectrum of patient experience. We examine challenges in evaluating decision-making capacity among individuals with ego-syntonic illnesses, especially when severely malnourished, recommend standardized, multidisciplinary, decision-specific protocols, and acknowledge that patients can retain capacity to make informed choices even when severely ill from an eating disorder. We review systemic barriers, including uneven access to specialized services and the impact of clinician moral distress, and suggest institutional supports such as ethics consultation and peer supervision. Finally, we outline an integrated model that combines specialized eating disorder treatment with palliative principles grounded in supported decision-making, emphasizing autonomy and hope. Research and training priorities include standardizing capacity-assessment tools, developing curricula on clinician resilience and ethics, evaluating outcomes of combined palliative-eating disorder interventions, and co-creating guidelines with lived-experience stakeholders. By focusing on actionable next steps, this commentary aims to guide ethical discourse and strengthen compassionate, equitable care for those who decline recommended interventions.